Cloud-Based Smart Attendance System: Design, Implementation, and Architecture (International Journal of Latest Technology in Engineering Management & Applied Science, 2026)
This paper proposes the design and implementa- tion of an integrated, cloud-based Smart Attendance System, specifically designed to meet the growing demands of modern educational institutions. The proposed Smart Attendance System is designed to incorporate two-factor authentication with facial recognition and RFID card identification to improve authenti- cation accuracy. The proposed Smart Attendance System em- ploys microcontroller technology, which may include NodeMCU ESP8266 or Raspberry Pi, in conjunction with MFRC522 RFID card identification module and camera configurations. The pro- posed facial recognition and detection are achieved by employing OpenCV or cloud-based APIs, while attendance is synchronized using cloud platforms like Firebase or AWS. The experimental results show a 99.4% authentication accuracy, reduced ad- ministrative burden, and improved accessibility compared to traditional manual attendance systems.